ESTIMASI CADANGAN KARBON BAWAH PERMUKAAN LAHAN GAMBUT DI DESA CATUR RAHAYU KECAMATAN DENDANG KABUPATEN TANJUNG JABUNG TIMUR - Anggi Septian; Heri Junedi; Agus Kurniawan Mastur (Jurnal Tanah dan Sumberdaya Lahan, 2023)
One of the functions of peatlands is as a hydrological function and plays an important role in the biosphere system as a carbon source controlling CO2 circulation and has a major influence on the balance of carbon in the earth's atmosphere. This study aimed to predict the magnitude of subsurface carbon stocks in peatlands in Catur Rahayu Village, Dendang District, East Tanjung Jabung Regency, Jambi Province. This study was carried out using a survey method with a map scale of 1: 25,000. Determination of sampling was in a grid that was made perpendicular to the drainage channel. The grid was made with a distance of 500 m x 250 m. Parameters observed as the main data included field measurements, namely land area (base map), peat thickness (drilling), peat decomposition level (van post method), C-organic (loss on ignition method), and bulk density (ring sample). Calculation of carbon stocks was carried out at a depth of each layer of peat decomposition level with calculations based on geographic information system (GIS) spatial modeling. The results of measuring carbon stocks in the soil in this study were related to using a combination of direct measurements in the field, laboratory results, and GIS spatial modeling-based calculations. The estimation of carbon stocks community land research in Catur Rahayu Village, the total carbon stock stored is 1,514.495.57 t, equivalent to 1,552.53 t ha-1.